Integrating evolutionary aspects into dual-use discussion: the cases of influenza virus and enterohemorrhagic Escherichia coli. Issue 1 (26th October 2021) - Gati, Noble Selasi; Altinok, Ozan Altan; Kumar, Sriram; Ferrando, Verónica A; Kurtz, Joachim; Quante, Michael; Ludwig, Stephan; Mellmann, Alexander
Abstract: Research in infection biology aims to understand the complex nature of host–pathogen interactions. While this knowledge facilitates strategies for preventing and treating diseases, it can also be intentionally misused to cause harm. Such dual-use risk is potentially high for highly pathogenic microbes such as Risk Group-3 (RG3) bacteria and RG4 viruses, which could be used in bioterrorism attacks. However, other pathogens such as influenza virus (IV) and enterohemorrhagic Escherichia coli (EHEC), usually classified as RG2 pathogens, also demonstrate high dual-use risk. As the currently approved therapeutics against these pathogens are not satisfactorily effective, previous outbreaks of these pathogens caused enormous public fear, media attention and economic burden. In this interdisciplinary review, we summarize the current perspectives of dual-use research on IV and EHEC, and further highlight the dual-use risk associated with evolutionary experiments with these infectious pathogens. We support the need to carry out experiments pertaining to pathogen evolution, including to gain predictive insights on their evolutionary trajectories, which cannot be otherwise achieved with stand-alone theoretical models and epidemiological data. However, we also advocate for increased awareness and assessment strategies to better quantify the risks-versus-benefits associated with such evolutionary experiments. In addition to building public trust in dual-use research, we propose that these approaches can be extended to other pathogens currently classified as low risk, but bearing high dual-use potential, given the particular pressing nature of their rapid evolutionary potential. Lay Summary: Scientific research is usually conducted for the good of humanity, e.g. to promote health and cure and prevent diseases. However, it can also intentionally be misused, and this potential is called 'dual-use'. We discuss this issue with special emphasis on evolution exemplified with two pathogens in an interdisciplinary manner from a biological and philosophical perspective.